Phenylpropanoids as naturally occurring antioxidants: From plant defense to human health - Korkina, L.G. (Cellular and Molecular Biology, 2007)
Phenylpropanoids (PPs) belong to the largest group of secondary metabolites produced by plants, mainly, in response to biotic or abiotic stresses such as infections, wounding, UV irradiation, exposure to ozone, pollutants, and other hostile environmental conditions. It is thought that the molecular basis for the protective action of phenylpropanoids in plants is their antioxidant and free radical scavenging properties. These numerous phenolic compounds are major biologically active components of human diet, spices, aromas, wines, beer, essential oils, propolis, and traditional medicine. Last few years, much interest has been attracted to natural and synthetic phenylpropanoids for medicinal use as antioxidant, UV screens, anticancer, anti-virus, anti-inflammatory, wound healing, and antibacterial agents. They are of great interest for cosmetic and perfume industries as active natural ingredients. In the present review, the metabolic pathways of phenylpropanoid biosynthesis in plants and the mechanism of phenylpropanoid-mediated plant defense are described. Learning from plants, free radical-driven, molecular and cellular processes modulated by phenylpropanoids in human cell cultures in vitro and in the in vivo animal models of tumors, inflammation, and cellular damage are also reviewed